ANALYSIS OF THE EFFECT OF RISK AWARENESS AND FINANCIAL LITERACY ON FIRE INSURANCE OF MSME OWNERS IN KUALUH LEIDONG DISTRICT, LABURA REGENCY - Putri Wulandini Sagala; Yenni Samri Juliati Nasution; Andri Soemitra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
Based on the results of the study on the influence of Risk Awareness and Financial Literacy on the decision to take fire insurance on MSME owners in Kualuh Leidong District, it can be concluded that both independent variables have a significant effect on the dependent variable. The Risk Awareness variable (X₁) shows a positive and significant effect on the decision to take fire insurance, with a t-value of 9.121 and a significance of 0.000